Sensitive, automatic method for the determination of diazepam and its five metabolites in human oral fluid by online solid‐phase extraction and liquid chromatography with tandem mass spectrometry. Issue 10 (6th May 2016) - Jiang, Fengli; Rao, Yulan; Wang, Rong; Johansen, Sys Stybe; Ni, Chunfang; Liang, Chen; Zheng, Shuiqing; Ye, Haiying; Zhang, Yurong
Abstract : A novel and simple online solid‐phase extraction liquid chromatography‐tandem mass spectrometry method was developed and validated for the simultaneous determination of diazepam and its five metabolites including nordazepam, oxazepam, temazepam, oxazepam glucuronide, and temazepam glucuronide in human oral fluid. Human oral fluid was obtained using the Salivette ® collection device, and 100 μL of oral fluid samples were loaded onto HySphere Resin GP cartridge for extraction. Analytes were separated on a Waters Xterra C18 column and quantified by liquid chromatography with tandem mass spectrometry using the multiple reaction monitoring mode. The whole procedure was automatic, and the total run time was 21 min. The limit of detection was in the range of 0.05–0.1 ng/mL for all analytes. The linearity ranged from 0.25 to 250 ng/mL for oxazepam, and 0.1 to 100 ng/mL for the other five analytes. Intraday and interday precision for all analytes was 0.6–12.8 and 1.0–9.2%, respectively. Accuracy ranged from 95.6 to 114.7%. Method recoveries were in the range of 65.1–80.8%. This method was fully automated, simple, and sensitive. Authentic oral fluid samples collected from two volunteers after consuming a single oral dose of 10 mg diazepam were analyzed to demonstrate the applicability of this method.